Culture of peace from the classroom. A meeting between Potter and Freire - Chaparro Barrera, Alida (Sociedad y Economía, 2018)
This review article reflects on Van Rensselaer Potter’s bioethics and Paulo Freire’s liberation pedagogy, and some similarities and differences that interact as foundations to promote a culture of peace. The objectives are to identify the position of both authors, establishing interactions between their postulates, and defining strategies that support a culture of peace and commitment from education. The bibliographic path that supports the project “Between bioethics and pedagogy of liberation, proposal of education for peace in Colombia” is presented. A qualitative methodology was used, towards the orientation of the bibliographic revision, with comparative analysis supported in the hermeneutic method that makes possible the understanding of terms and meanings; for the record of the information the content-card file was used. It is concluded that to begin to consolidate a culture of peace from the classroom, solid theoretical bases, reformulation of curricula, and curricula and public policies are required, to enable relevant and inclusive social and pedagogical projects that transform the daily violence spheres.